(untitled) (Medico Legal Update, 2019)
Deaths occurring in police custody incite enormous amount of emotions from relatives of deceased and speculations from media and general public. A person in custody is entirely dependent on his custodians for his basic requirements; hence this type of death raises questions regarding living conditions, inhumane treatment and violation of fundamental rights of prisoners. This prospective observational study was carried out during period April 2017 to March 2018 in Department of Forensic Medicine, at SMS Medical College, Jaipur, Rajasthan. 20 cases of alleged Deaths in custody during study period were observed on the subjects of socio-demographic profile of deceased, circumstances prior to deaths, treatment taken, postmortem findings and cause of deaths. The data so obtained was statistically analysed. This study observed that maximum cases were male (95%); age group above 61 years (30%); urban domicile (65%). Maximum cases were brought in month of February (25%) followed by January (20%). Most prisoners died in hospital during treatment (80%). Natural causes of death were commoner than unnatural causes. Histopathological observations were most common for carcinoma (25%) followed by myocardial infarction (20%).